Contemporary approaches and future perspectives of antibacterial photodynamic therapy (aPDT) against methicillin-resistant Staphylococcus aureus (MRSA): A systematic review - Dharmaratne, Priyanga; Sapugahawatte, Dulmini Nanayakkara; Wang, Baiyan; Chan, Chung Lap; Lau, Kit-Man; Lau, Clara BS; Fung, Kwok Pui; Ng, Dennis KP; IP, Margaret (European journal of medicinal chemistry, 2020)
The high prevalence of methicillin-resistant Staphylococcus aureus (MRSA) causing skin and soft tissue infections in both the community and healthcare settings challenges the limited options of effective antibiotics and motivates the search for alternative therapeutic solutions, such as antibacterial photodynamic therapy (aPDT). While many publications have described the promising anti-bacterial activities of PDT in vitro, its applications in vivo and in the clinic have been very limited. This limited availability may in part be due to variabilities in the selected photosensitizing agents (PS), the variable testing conditions used to examine anti-bacterial activities and their effectiveness in treating MRSA infections. We thus sought to systematically review and examine the evidence from existing studies on aPDT associated with MRSA and to critically appraise its current state of development and areas to be addressed in future studies. In 2018, we developed and registered a review protocol in the International Prospective Register of Systematic Reviews (PROSPERO) with registration No: CRD42018086736. Three bibliographical databases were consulted (PUBMED, MEDLINE, and EMBASE), and a total of 113 studies were included in this systematic review based on our eligibility criteria. Many variables, such as the use of a wide range of solvents, pre-irradiation times, irradiation times, light sources and light doses, have been used in the methods reported by researchers, which significantly affect the inter-study comparability and results. On another note, new approaches of linking immunoglobulin G (IgG), antibodies, efflux pump inhibitors, and bacteriophages with photosensitizers (PSs) and the incorporation of PSs into nano-scale delivery systems exert a direct effect on improving aPDT. Enhanced activities have also been achieved by optimizing the physicochemical properties of the PSs, such as the introduction of highly lipophilic, poly-cationic and site-specific modifications of the compounds. However, few in vivo studies (n = 17) have been conducted to translate aPDT into preclinical studies. We anticipate that further standardization of the experimental conditions and assessing the efficacy in vivo would allow this technology to be further applied in preclinical trials, so that aPDT would develop to become a sustainable, alternative therapeutic option against MRSA infection in the future. [Display omitted] •There are 113 studies being reported for aPDT against MRSA.•Cationic PSs are effective in aPDT against MRSA.•PSs linking with IgG, antibody, efflux pump inhibitors and bacteriophage increase the potency of aPDT against MRSA.•There are still but few in vivo aPDT studies that had been carried out against MRSA infections (n = 17).